1999
DOI: 10.1017/s0081305200028867
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of Water Quality in Livestock Regions: An Application to Rural Watersheds in Iowa

Abstract: This paper investigates rural residents' perceptions of the risk to water quality from large confinement facilities and their willingness to pay to delay nitratecontamination from these facilities. Rural residents are concerned about the environmental impact of confinement facilities and are willing to pay as much as $82 annually to delay nitratecontamination in their water for 20 years. These contingent valuation results are consistent with the result obtained in similar studies that used hedonic valuation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…These authors also found that the likelihood of a respondent remaining in an area for another five years positively influenced the median WTP to delay nitrate contamination. Hurley, Otto and Holtkamp (1999) assert that the results obtained in this study are similar to those obtained using the hedonic pricing method.…”
Section: Water Quality Contingent Valuation Studiessupporting
confidence: 83%
See 3 more Smart Citations
“…These authors also found that the likelihood of a respondent remaining in an area for another five years positively influenced the median WTP to delay nitrate contamination. Hurley, Otto and Holtkamp (1999) assert that the results obtained in this study are similar to those obtained using the hedonic pricing method.…”
Section: Water Quality Contingent Valuation Studiessupporting
confidence: 83%
“…Numerous studies have examined water quality issues using a variety of techniques including CV (Brox, Kumar and Stollery, 2003;Collins, Rosenberger and Fletcher, 2005;Eisen-Hecht and Kramer, 2002;Hurley, Otto, Holtkamp, 1999;Loomis et al, 2000;Stumborg, Baerenklau and Bishop, 2001;Whitehead, 2000) (Table 2.1).…”
Section: Water Quality Contingent Valuation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These minimum monetary values can be compared with various assessments of the costs associated with specific damages for specific regions. For example, Hurley et al (1999) found that rural residents of Iowa are willing to pay up to $82 annually to reduce contamination in their water for a period of 20 years. Results of Sukharomana (in Intarapapong 1999) indicated averting expenditures and willingness to pay of consumers to avoid nitrate contamination in groundwater of $9.12 and $6.12 per month per household.…”
Section: Introductionmentioning
confidence: 99%